2007
DOI: 10.1007/s11606-007-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Delays for Research Training in Medical School are Associated with Poorer Subsequent Clinical Knowledge

Abstract: BACKGROUND:Complementary degree programs and research training are important alternative tracks in medical school that typically interrupt the traditional MD curriculum. OBJECTIVE:Examine effects of such a break on clinical knowledge after reentry into the MD curriculum. DESIGN:Retrospective cohort study. PARTICIPANTS:Three hundred and two graduates of Mayo Medical School. MAIN MEASUREMENTS:Compared years of delay between the second and third years of medical school with third year clerkship grades, National B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Both of these outcomes are explorative in nature (rely on proportions rather than odds ratios) and have been quantitatively pooled to yield a weighed estimate value. The results have been summarized in Fig 3 [ 7 , 10 , 26 , 28 , 32 , 47 49 , 52 , 54 , 55 , 58 , 63 , 67 69 , 71 – 75 , 80 82 , 85 , 90 92 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Both of these outcomes are explorative in nature (rely on proportions rather than odds ratios) and have been quantitatively pooled to yield a weighed estimate value. The results have been summarized in Fig 3 [ 7 , 10 , 26 , 28 , 32 , 47 49 , 52 , 54 , 55 , 58 , 63 , 67 69 , 71 – 75 , 80 82 , 85 , 90 92 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Dyrbye et al found that a delay of 3 years or more during medical school for research was associated with lower grades and scores on clinical knowledge tests (Dyrbye et al 2007). In addition, Tait et al found that students undertaking an intercalated degree had no consistent short-term academic advantage over those who did not (Tait & Marshall 1995).…”
Section: Challenges and Solutions To Medical Student Researchmentioning
confidence: 99%
“…Problem solving is key, where incomplete and perhaps conflicting information needs to be synthesized and processed effectively. In our undergraduate medicine curriculum, we aim to establish a learner-centred experiential approach, which is educationally beneficial [6, 7] to develop deep learning with higher order intellectual skills and attributes, and improve clinical diagnostic skills and pattern recognition from within an integrated curriculum [8, 9]. Research skills can be superficially offered as a series of lectures, workshops and small-group work, applying a range of techniques.…”
Section: Introductionmentioning
confidence: 99%